THE LEGAL NATURE OF JUS COGENS IN CONTEMPORARY INTERNATIONAL LAW (Georgian Journal for European Studies, 2017)
Almost forty years I have been watching developments taking place in international law doctrinal approaches and activities of international  and domestic judicial bodies referring to interna onal jus cogens, the concept of which had emerged during the work of Interna onal Law Commission (ILC)  (1963-1966) on the ar cles of the law of trea es, later embodied in the Vienna Conven on on the Law of Trea es.It can be easily noticed that unlike the previous period (1963-1980),  contemporary  judicial and dip- lomatic practices contain many references  to jus cogens. Indeed, while working on this topic the ILC had to base its judgments  on purely doctrinal contributions contained  in publications or submitted papers by international law experts and comments made by the States, because there had not been a single judicial case on this subject matter.Despite of this fact, the ILC had managed to oﬀer a well-elaborated  draft on the issue of peremptory norms (jus cogens) resulted in Articles 53 and 64 of the Vienna Convention on the Law of Treaties.  At the first glace it seems, that we had been witnessing  progressive  events aimed at further developing  of the concept based on practical cases and pragmatic doctrinal suggestions interpreting these cases.Unfortunately,  I cannot share such an optimistic view, because contemporary  approaches  ignore the real legal notion, that had been formed during the centuries  beginning  from the ancient time. The main mistake, in my understanding,  consists in misunderstanding of the core of the legal notion of jus cogens. Jus cogens has nothing in common with the legal notion of violation (breach) of international law, that is, it deals only with the international law-making process, since every rule of international law cannot be violated by States, even if it has a character of jus dispositivum allowing States to change a legally binding rule. Only international jus cogens norm cannot be changed by the States inter se, if it is recognized and accepted by the international community as a whole as a norm, any derogation from which (to make a diﬀerent legal rule) by states is forbidden.1I would  not touch  upon these,  in my understanding,  wrong  approaches,  which  ignore  this specific character of jus cogens, having nothing in common with the deeds of the States and is concerned with the content of a new rule which is supposed to be established by the individual States in their mutual relations. That is why I decided to remind the international community  and authors of contemporary  doctrinal and judicial approaches  the events of 1960s while the International Law Commission  was drafting the Articles53 and 64.  (The more detailed and comprehensive  analysis of contemporary  approaches will be oﬀered in a special publication).